An evaluative study on the news releases of Mindanao Economic Development Council from February to March 2009 - Castro, Karen Kae M.
In public relations process, evaluation is presented last but it is not the final step. Rather, it is the beginning of a new public relation process. The study aims to evaluate the news releases of Mindanao Development Council (MEDCo) from February to March 2009. The researcher did a content analysis on the 47 news releases using Gunning Fog Index for the readability test and framing to identify the frame and framing mechanisms used. The results were then compared to the expectations from the 3 writers of the three major local newspapers in Davao City. The results of study show that (1) news releases of MEDCo are difficult to read and demands more attention from readers for comprehension; (2) the themes and frames are consistent with the nature and the objective of MEDCo and OCMA; (3) OCMA?s generation of media support activities such as exhibits, media coverage/mobilization, quiz shows is the most satisfied objective thus making it the most effective public relations strategy.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Speech Communication